Factorial Design Assisted pH-independent Delivery System of Poorly Soluble Drug Cinnarizine - M. Mehta, Dharmik (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: This study aims to overcome pH-dependent solubility, a common problem observed in poorly soluble BCS (biopharmaceutics classification system) Class II drugs. Materials and Methods: A model drug, cinnarizine, was selected for the study to formulate oral multiunit pH-independent delivery system utilizing mucoadhesion as an intestine retention technique. Microenvironment pH modulation mechanism was utilized to ensure pH-independent delivery at varying gastric fluid pH conditions. The formulation was developed in the form of modified release capsule, comprising three components (i) fast dissolving granules, (ii) multilayer alginate beads (AB), and (iii) erodible capsule plug (EP). Fast dissolving granules were formulated by trial and error method. Other two components were optimized by applying 3 × 2 full factorial design. Independent variables selected for AB were HPMC K4M and Noveon® AA-1 while that of EP were HPMC K100LV and Polyox® 303 WSR. Dependent variables selected for AB were percentage drug release at 2 h (Q2h), 4 h (Q4h), 8 h (Q8h) and mucoadhesion potential. For EP, dependent variables were erosion time, floating lag time and total floating time. Surface pH of multilayer AB was measured at regular time interval to ascertain acidic microenvironment. Results and Discussion: Optimized components were filled into Eudragit® L 100-55 coated hard gelatin capsule body. Optimized capsule formulation (OP) was characterized by relevant evaluation parameters, pH-independent drug release, and stability study. In vitro drug release profile of OP showed pH-independent release and followed Weibull release kinetic model. Conclusion: Drug delivery of pH-dependent poorly soluble drug to upper GI tract was successfully formulated to overcome problem of pH-dependent solubility